A Comparative Analysis of Clinical Presentation, Prognosis and Outcomes in Paralytic Dogs with a Compressive and a Contusive Intervertebral Disc Disease - Anna Kurtscheidt; Stefan Rupp; Ute Müller; Franck Forterre (Veterinary Sciences)
This retrospective study aims to investigate whether dogs with a contusive and dogs with a compressive intervertebral disc disease share comparable outcomes and prognoses when presenting with the same neurological grade. A total of 50 dogs with IVDE (compression group) and 45 dogs with ANNPE (contusion group) were included in this study. The protocol involved a thorough review of the medical records and CT/MRI images of the included dogs. Data encompassing signalment, initial clinical signs, post-diagnosis treatment and short-term outcomes (less than 8 months) were collected from the patient records. Information on long-term outcomes (more than 8 months) was obtained through interviews with the owners. Dogs in the compression group displayed clinical signs at a statistically significant younger age and were more likely to experience deteriorating neurological deficits compared to the contusion group. Conversely, dogs with contusions had a significantly higher incidence of external trauma history and vocalization at the onset of clinical signs. In both groups, the most affected spinal cord segment was T3-L3. The overall recovery rate to regain independent ambulation was 71% in the contusion group vs. 80% in the compression group. While some of the examined parameters revealed differences, most did not significantly differ between the groups.